Advances and challenges of immunocheckpoint inhibitors in the treatment of primary liver cancer - Hu, Meng; Yao, Weirong; Shen, Qinglin (Frontiers in Genetics, 2022)
Primary liver cancer (PLC) is one of the most common malignant tumors, which clinically characterized by occult onset, rapid development, easy recurrence and poor prognosis. With the rapid development of tumor immunotherapy research, tumor immunotherapy has also achieved remarkable clinical efficacy, and jointly promoted the overall improvement of tumor immunology from mechanism research to clinical transformation, from single discipline to multi-disciplinary integration. Immunotherapy has obvious advantages in treatment-related toxicity and efficacy compared with traditional therapy. In hepatocellular carcinoma (HCC), immunotherapy alone or in combination with other therapies may help to control tumor progression, and there are many immune checkpoint inhibitors (ICIs) widely used in clinical or ongoing clinical trials. However, tumor immunology research is still facing many challenges. How to effectively evaluate the efficacy, whether there are related biomarkers, the generation of immune tolerance and the lack of clinical trials to objectively evaluate the efficacy are still urgent problems to be solved, but it also brings new research opportunities for basic and clinical immunology researchers. The study of treatment of ICIs of PLC has become a hot spot in clinical research field. This paper summarizes and prospects the research progress and challenges of ICIs for PLC.